Practices on Menstrual hygiene management among girls aged 9 to 17 years in Mathioya sub-county, Murang'a County. - NYARENCHI, JANET BOSIBORI (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Menstrual hygiene is crucial for women, especially in underdeveloped countries, but many face challenges in homes, schools, and workplaces. Rural girls often lack knowledge about menstruation, leading to unacceptable behaviors. Limited data exists on economically disadvantaged adolescent females in Mathioya sub-county, Murang'a County. The study aimed to assess personal hygiene habits, menstrual management materials, and disposal techniques for improving menstrual hygiene practices and overall well-being among adolescent girls in the region using a descriptive cross-sectional design and stratified random sampling technique. A study of 387 adolescent females aged 9–17 years found that 80% of them adhered to proper personal hygiene practices, with 94% changing their menstrual products every 4–6 hours. Most used soap and water for handwashing, while 86% used cloth, soap, and water for genitalia cleansing. 95% used disposable sanitary pads to manage menstrual periods, but faced challenges due to poverty. Only 92% preferred disposable pads, despite receiving information about other options. 85% of participants wished the government and ministry of education would offer complimentary sanitary products to address period poverty. 97% of participants believed pit latrines were the most efficient way to dispose of menstrual waste, but only 10% had the opportunity to use them. 83% of those unaware of the negative consequences of improper disposal were unaware of the adverse effects. The study highlights the need for improved sanitary products and education programs to address period poverty. The study suggests integrating menstrual hygiene management into the National School Health strategy to improve personal hygiene behaviors among girls, as well as collaborating with the Murang'a county government and school administration for sanitary items and waste disposal materials.